2007
DOI: 10.1177/1098611107299393
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Crime Analysis Into Law Enforcement Agencies

Abstract: The purpose of this article is exploratory and it seeks to depict how crime analysts perceive patrol officers' and other sworn police officers' attitudes about the crime analysis function and its "organizational fit" as well as their own attitudes about sworn personnel. These issues were explored with data collected through an online survey of crime/intelligence analysts. The main findings are that most analysts felt that management was fairly supportive of their work, but that their perceptions of what patrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Cope (2004) reports that since most of the analysts in the UK are civilian, their products are often overlooked by police officers. Previous research indicated that analysts perceive officers' attitudes towards them as neither positive nor negative (Taylor et al 2007). Our research suggests that things had moved on since then and there was far more acceptance of analysts' skills and abilities even though their recommendations might often be overlooked.…”
Section: Analytical Capacity and Contributionmentioning
confidence: 53%
See 2 more Smart Citations
“…Cope (2004) reports that since most of the analysts in the UK are civilian, their products are often overlooked by police officers. Previous research indicated that analysts perceive officers' attitudes towards them as neither positive nor negative (Taylor et al 2007). Our research suggests that things had moved on since then and there was far more acceptance of analysts' skills and abilities even though their recommendations might often be overlooked.…”
Section: Analytical Capacity and Contributionmentioning
confidence: 53%
“…However, the difference between crime and intelligence analysis was much less well understood. Previous research suggests perception of the difference between crime analysts and intelligence analysts was one of scope: one more narrowly focused on problem-solving and resource allocation, while the other used a wider array of data sources and specialist analytical skills to aid investigation, detection and prosecution (Taylor et al 2007). Our research found that the difference between the roles was less clear-cut, suggesting that the division between crime analysis and intelligence analysis is becoming blurred.…”
Section: Role Description and Contentmentioning
confidence: 66%
See 1 more Smart Citation
“…Well that's what they say, get rid of the guy that's just come to the DIU [Divisional Intelligence Unit] to retire and doesn't want to do anything." It is well-documented that intelligence analysis has historically been marginalized by frontline officers, detectives, and senior management (Cope, 2004;O'Shea & Nicholls, 2002;Sanders et al, 2015;Taylor, Kowalyk, & Boba, 2007), suggesting that placing disinterested officers into intelligence positions undermines the value of intelligence analysis. Many interviewees, however, felt that one of the key factors contributing to poor working relationships between some analysts and detectives is that many investigators do not fully understand what intelligence is and, in particular, what analysts can actually do for them.…”
Section: Analysts and Decision Makersmentioning
confidence: 99%
“…Data analysis involves processing raw data into useful information upon which conclusions can be drawn (Adè r & Mellenbergh, 2008). Techniques for data analysis were arranged in four dominant categories: time series analysis, pattern matching, explanation-building and program logic models (Tabachnick & Fidell, 2007;Adè r & Mellenbergh, 2008). The qualitative aspect of this research was analyzed by following the "explanation-building" technique and an interpretational method was adopted to analyze the data collected.…”
Section: Discussionmentioning
confidence: 99%